A clean and efficient approach for recovery of vanadium and tungsten from spent SCR catalyst. (1st May 2021) - Cao, Yijun; Yuan, Junfan; Du, Hao; Dreisinger, David; Li, Meng
Highlights: An efficient and oxidation hydrometallurgical method was developed in this work. The mechanisms of V and W species extraction processes were conducted. The regenerated SCR catalyst was almost recovered with Nitric Oxide conversion of 92%. Abstract: The widespread use of selective catalytic reduction (SCR) catalysts will provide many waste SCR catalysts. These spent catalysts can be identified as hazardous solid waste because they contain a lot of heavy metals. This work aims to develop a clean, green, and economical way to recover valuable metals and regenerate the catalyst. The effect parameters of hydrogen peroxide and ammonium carbonate concentration, time, and temperature on the V and W leaching efficiencies were investigated. The leaching process can be described by a shrinking core model (SCM). The raw material and the residue were characterized by XRD, SEM-EDS, XPS, and Raman analysis. The crystal structure of the leaching residue was stable through the leaching process and can serve as a carrier for the regenerated catalyst. Ammonium paratungstate (APT) and vanadium pentoxide were obtained. This work may introduce a new perspective for the efficient and comprehensive usage of the spent SCR catalyst.